Analisis Faktor Stres Kerja Pegawai Honorer Generasi Y Pada Dinas Tenaga Kerja dan Transmigrasi Nusa Tenggara Barat - Ibrahim, Isra Dewi Kuntary; Rahmawati, Pebby; Cahyadi , Irwan (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Employees are resources that have an important role in the implementation of an organisation. So it is very important for companies to pay attention to the physical and psychological balance of employees. This study aims to analyse what factors affect job stress and the most dominant factor affecting job stress of generation Y honorary employees at the Manpower and Transmigration Office of West Nusa Tenggara Province. The population in this study were honorary generation Y employees totalling 62 people. The sampling technique in this study used nonprobability sampling technique with purposive sampling method where the sample determination used specific criteria, namely only generation Y honorary employees as many as 62 people. This type of research is quantitative research with an exploratory descriptive approach. This study found that leadership, tenure, dual role, career development, workload, interpersonal conflict, role demands and saturation are factors that cause job stress in generation Y honorary employees at the Department of Manpower and Transmigration. As for personality type A is not a factor causing work stress in generation Y honorary employees and career development is the most dominant factor affecting work stress. Suggestions in this study are that there are many employees of productive age can make these employees a forum for finding new ideas to develop the company.